Indonesia : Oil and Gas Sector Study - World Bank (Washington, DC, 2013)
This study attempts to provide a broad, first cut review of the most pressing issues facing the sector, and to recommend ways to ameliorate or eliminate the problems. The main problems are: 1) petroleum product prices are heavily subsidized at the aggregate level and distorted at relative levels, and thus need to be rationalized within an economic framework; 2) the functions and role of the state oil and gas company (Pertamina) are problematic, and therefore Pertamina must be fundamentally restructured to eliminate the conflicts of interest and inefficiencies; 3) some of the provisions of the production sharing contracts are relatively regressive and need to be re-evaluated with a view to maximize the contribution of the sector to the economy, and to increase upstream investment by the private sector; 4) existing laws and regulations are inadequate and must be replaced; 5) petroleum products are of poor quality and must be improved, particularly by phasing out the lead from gasoline; and 6) energy sector institutions are weak and must be strengthened. Although the issues are complex and sweeping changes are needed, given the current political climate, this is an opportune time for Indonesia to begin the process. As a first step, preparing an official and comprehensive declaration of government policy for the hydrocarbon sector is critically important--needed are the vision for the sector, policy objectives, and policy actions required to solve the sector's problems.